(untitled) (Jurnal Legislatif, 2024)
In recent developments, Indonesia, as a democratic nation, emphasizes the government by the people, for the people, and of the people. The core of this democracy is reflected in the electoral process conducted every five years, ensuring the cyclical nature of government based on the people’s mandate. However, the manipulation of the judicial system by the ruling government through the Supreme Court and Constitutional Court has raised concerns. This study investigates the phenomenon known as Abusive Judicial Review, where the judiciary, initially intended to oversee the hierarchy of laws and the constitution, is influenced by those in power. Utilizing normative legal research, this paper explores the extent to which judicial decisions can be swayed by political interests, thereby undermining democracy. The findings reveal that the judiciary’s independence is compromised, resulting in decisions that serve the interests of the ruling regime rather than upholding democratic principles. This study offers a critical analysis of significant cases and proposes measures to protect judicial integrity. The novelty of this research lies in its comprehensive examination of the systemic issues within Indonesia’s judiciary and its implications for democracy. The conclusion underscores the urgent need for reforms to safeguard the judicial process from political interference.